2019
DOI: 10.1111/1462-2920.14764
|View full text |Cite
|
Sign up to set email alerts
|

Improving eDNA‐based protist diversity assessments using networks of amplicon sequence variants

Abstract: Summary Effective and precise grouping of highly similar sequences remains a major bottleneck in the evaluation of high‐throughput sequencing datasets. Amplicon sequence variants (ASVs) offer a promising alternative that may supersede the widely used operational taxonomic units (OTUs) in environmental sequencing studies. We compared the performance of a recently developed pipeline based on the algorithm DADA2 for obtaining ASVs against a pipeline based on the algorithm SWARM for obtaining OTUs. Illumina‐sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 86 publications
(159 reference statements)
4
49
0
Order By: Relevance
“…We used both the original ASV data and ASV-clusters for downstream analysis. This ASV-clustering approach was preferred over the traditional OTU clustering: ASVs reduce false positive rates more than most OTU clustering approaches and therefore result in a more accurate phylogenetic tree and more accurate, tractable clusters [57][58][59][60] .…”
Section: Methodsmentioning
confidence: 99%
“…We used both the original ASV data and ASV-clusters for downstream analysis. This ASV-clustering approach was preferred over the traditional OTU clustering: ASVs reduce false positive rates more than most OTU clustering approaches and therefore result in a more accurate phylogenetic tree and more accurate, tractable clusters [57][58][59][60] .…”
Section: Methodsmentioning
confidence: 99%
“…Forster et al . () processed haplotypes of 29 ciliate species with DADA2 (Callahan et al ., ) and SWARM (Mahé et al ., ) and observed that both methods required additional haplotype grouping to reach congruency with morphological data. Results of Dunthorn et al .…”
Section: Discussionmentioning
confidence: 99%
“…Many of the novel or rare OTUs mentioned above could be artifacts produced during sequencing and/or sequence grouping, and thus, additional postclustering quality filters are recommended (Forster et al. ; Frøslev et al. ).…”
Section: What Have We Learned With and About Metabarcoding?mentioning
confidence: 99%